In vitro antioxidant effects of hydroalcoholic extract of Cassia tora aerial part using different models - Umesh Chaurasia; Vishal Soni; Ram Kumar Sahu (Creative Pharma Assent, 2024)
Background: Free radicals, harmful by-products of a cell's natural metabolism, are responsible for various health problems. The search for plant-based supplements or medicines is always in high demand, as is the antioxidant activity that contributes to the therapeutic efficacy of plants. Aim: In the present study, the hydroalcoholic extracts from the aerial parts of Cassia tora were used for in vitro analysis of their antioxidant activity. Methods: Six separate assay methods were used to evaluate the antioxidant activity, i.e., against hydroxyl radical, DPPH, superoxide anions, nitric oxide, and also total flavonoid and phenolic content, were investigated. This was done by standardizing hydroalcoholic extract (70/30 ethanol to water) of Cassia tora and ascorbic acid. Results: Percentage scavenging activity and IC50 value were measured for extract prepared at various concentrations. The results IC50 values were 25.54 µg/ml, 45.04 µg/ml, 36.56 µg/ml, and 97.61 µg/ml for DPPH, superoxide radicals, hydroxyl radicals, and nitric oxide, respectively. Subsequently, the total phenolic and flavonoid content in the extract obtained was 1.927±0.73 mg GAE/gm and 1.018±0.29 mg QE/gm, respectively. Conclusion: The hydroalcoholic extract of Cassia tora contains more phytoconstituents. This suggests it has a wide range of medicinal antioxidant properties that make it helpful in treating many diseases. With the increasing demand for safer herbal treatments, scientific efforts in this field are making significant contributions and advances and supporting innovation.